Polyethylene and articles thereof

The processing and rheology challenges of existing polyethylene polymers are solved by developing a polyethylene copolymer with a density of 0.934 g/cm3 to 0.945 g/cm3 and a melt index of 0.9 g/10 min to 2.5 g/10 min, and better processability and bubble stability are achieved.

CN119855843APending Publication Date: 2025-04-18EXXONMOBIL CHEMICAL PATENTS INC
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
CN202380064497.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-07
Filing Date
2023-08-07
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing polyethylene polymers have challenges in processing and rheology, including bubble instability due to low melt viscosity and melt rupture at high shear rates.

Method used

A polyethylene copolymer was developed that contains a density of 0.934 g/cm3 to 0.945 g/cm3, a melt index of 0.9 g/10 min to 2.5 g/10 min, a composition distribution width index of 75% or more, a molecular weight distribution of 2 to 8 and a melt index ratio of 30 to 75. The copolymer has a high viscosity at low shear rates, improving processability and bubble stability.

Benefits of technology

It is achieved to improve the processability and bubble stability of polyethylene copolymers at commercial shear rates, reduce the tendency of melt rupture, and improve the production efficiency of blown films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855843A_ABST
    Figure CN119855843A_ABST
Patent Text Reader

Abstract

The present disclosure relates generally to polyethylene polymers and articles made therefrom. In some embodiments, the polyethylene copolymer includes ethylene units, and from 1% to 8% by weight of C3-C8 alpha-olefin comonomer units. The polyethylene copolymer has a density of from 0.934 g / cm3 to 0.945 g / cm3, a melt index (MI, determined according to ASTM D1238 at 190 DEG C and 2.16 kg load) of greater than 1 g / 10 min and less than or equal to 2.5 g / 10 min, a compositional distribution width index of 75% or greater, a molecular weight distribution (MWD, Mw / Mn) of from 2 to 8, and a melt index ratio (MIR) in the range of from 30 to 75, where MIR is the ratio of high load melt index (HLMI, ASTM D1238 at 190 DEG C, 21.6 kg) to melt index (MI, ASTM D1238 at 190 DEG C, 2.16 kg).
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims the benefit of U.S. Provisional Application No. 63 / 374,856, filed on September 7, 2022, entitled “Polyethylene and Articles Thereof,” the entire contents of which are incorporated herein by reference. Technical Field

[0002] The present disclosure relates generally to polyethylene polymers and articles made therefrom. Background Art

[0003] Medium density polyethylene polymer (or resin) is used in applications such as laminated composite pipes (lamitube), blown breathable films, waterproof sheets and pipe adhesives. In order to achieve high throughput during processing, it is desirable that polymers have a low melt rate under those shear rates that are usually encountered during extrusion and melt processing. Polymers with high melt index (lower molecular weight) can usually show required low melt viscosity within the extrusion shear rate range. However, this high melt index polymer also shows low melt viscosity under relatively low shear rates (for example, under zero shear viscosity), which will result in poor bubble stability during processing. Other polyethylene polymers are known, such as linear low density polyethylene (LLDPE) and low density polyethylene (LDPE), both of which have some properties that may be advantageous and other properties that may be unfavorable for processing.

[0004] LLDPE is a substantially linear polymer made of ethylene monomer units and α-olefin comonomer units such as 1-butene or 1-hexene. Unlike conventional LDPE containing a large amount of long chain branches extending from the polymer backbone, LLDPE has little or no detectable long chain branching (LCB) per 1,000 carbon atoms. Long chain branching provides reduced neck-in and increased draft stability during extrusion. In addition, relative to LDPE, LLDPE has a narrower molecular weight distribution (MWD), as well as different rheological and mechanical properties, such as tear properties. LLDPE and LDPE are also produced via different manufacturing processes.

[0005] LLDPE formed using metallocene catalysts is called "mLLDPE". Extrusion of mLLDPE generally requires more motor power and higher extruder pressure to match the extrusion rate of LDPE. Typical mLLDPE also has lower melt strength, which, for example, adversely affects bubble stability during blown film extrusion. Typical mLLDPE is also prone to melt fracture at commercial shear rates. Melt fracture is a flow disturbance that causes surface roughness and / or surface irregularities in the extruded resin, which involves severe deformation of the extrudate. Melt fracture occurs when the shear stress imparted to the resin exceeds the critical shear stress value of the resin or when slip-stick flow conditions occur in the die. Melt fracture can be associated with high die shear rates (e.g., 1,000-60,000 s -1 ) is related to shear stress. The high shear rate is a result of the high line speeds (e.g., >600 m / min) used to achieve mLLDPE films.

[0006] Increased melt strength is a desirable attribute for many polyolefin applications, including films. Higher melt strength allows manufacturers to run blown film lines at faster rates to form films of mLLDPE.

[0007] Regardless of the above processing and rheological challenges, mLLDPE does exhibit superior physical properties compared to LDPE. In the past, various levels of LDPE have been blended with mLLDPE to, for example, increase melt strength, increase shear sensitivity, increase fluidity at commercial shear rates in extruders, and reduce the tendency to melt fracture. However, such blends typically have poor mechanical properties compared to neat mLLDPE. In fact, improving the processability of mLLDPE without sacrificing physical properties has always been a challenge. Comparing LLDPEs to each other, LLDPEs with higher melt indexes are better for processing, and the combination of higher melt index and lower density is particularly suitable for cast film applications. However, less long chain branching—as presented by conventional LLDPE—can result in reduced film properties.

[0008] In general, finding polyethylene copolymers that have the right balance of melt index and density while being commercially processable is challenging.

[0009] References that may be of interest in this regard include: U.S. Patent Nos. 6,255,426; 7,951,873; 9,718,896 and 10,029,226; U.S. Patent Publication Nos. US2004 / 0121098; US20070260016; US2015 / 0232589 and US2020 / 0339715; and U.S. Application Serial No. 63 / 362,239.

[0010]

[0006] Thus, there remains a need for new polyethylene polymers having a combination of desirable properties (eg, density, melt index properties, long chain branching) while also providing the commercially desirable processability and extrusion of polyethylene polymers. Summary of the invention SUMMARY OF THE INVENTION

[0011] The present disclosure relates generally to polyethylene polymers and articles made therefrom.

[0012] In one embodiment, the polyethylene copolymer comprises ethylene units and 1 wt % to 8 wt % of C3-C8 α-olefin comonomer units. The polyethylene copolymer has a molecular weight of 0.934 g / cm 3 Up to 0.945g / cm 3 density; a melt index (MI; measured at 190°C and 2.16 kg load according to ASTM D1238) greater than 0.9 g / 10 min and less than or equal to 2.5 g / 10 min; a composition distribution width index of 75% or greater; a molecular weight distribution (MWD, Mw / Mn) of 2 to 8; and a melt index ratio (MIR) in the range of 30 to 75; wherein MIR is the ratio of a high load melt index (HLMI, ASTM D1238 at 190°C, 21.6 kg) to a melt index (MI, ASTM D1238 at 190°C, 2.16 kg).

[0013] In another embodiment, the article includes a polyethylene copolymer. The polyethylene copolymer includes ethylene units and 1 wt % to 8 wt % of C3-C8 α-olefin comonomer units. The polyethylene copolymer has a molecular weight of 0.934 g / cm 3 Up to 0.945g / cm 3 density; a melt index (MI; measured at 190°C and 2.16 kg load according to ASTM D1238) greater than 0.9 g / 10 min and less than or equal to 2.5 g / 10 min; a composition distribution width index of 75% or greater; a molecular weight distribution (MWD, Mw / Mn) of 2 to 8; and a melt index ratio (MIR) in the range of 30 to 75; wherein MIR is the ratio of a high load melt index (HLMI, ASTM D1238 at 190°C, 21.6 kg) to a melt index (MI, ASTM D1238 at 190°C, 2.16 kg).

[0014] In another embodiment, the cast film or blown film comprises a polyethylene copolymer. The polyethylene copolymer has a molecular weight of 0.935 g / cm 3 Up to 0.938g / cm 3 The density and melt index of 1.1 g / 10min to 1.3 g / 10min.

[0015] In another embodiment, the cast film or blown film comprises a polyethylene copolymer. The polyethylene copolymer has a molecular weight of 0.935 g / cm 3 Up to 0.938g / cm 3 The density and melt index of 1.8 g / 10 min to 2.0 g / 10 min.

[0016] In another embodiment, the laminated composite pipe includes a polyethylene copolymer. The polyethylene copolymer has a complex shear viscosity (η*) of 15,000 Pa·s to 25,000 Pa·s at 0.01 rad / s and 190°C, a complex shear viscosity (η*) of 1,100 Pa·s to 1,300 Pa·s at 100 rad / s and 190°C, and a viscosity of 0.935 g / cm 3 Up to 0.942g / cm 3 The density is and the melt index is 1 g / 10 min to 1.5 g / 10 min.

[0017] In another embodiment, a hygiene product includes a polyethylene copolymer. The polyethylene copolymer has a complex shear viscosity (η*) of 8,000 Pa·s to 10,000 Pa·s at 0.01 rad / s and 190° C., a complex shear viscosity (η*) of 900 Pa·s to 1,100 Pa·s at 100 rad / s and 190° C., and a viscosity of 0.935 g / cm 3 Up to 0.940g / cm 3 The density and melt index of 1.5 g / 10 min to 2.5 g / 10 min.

[0018] In another embodiment, a pre-applied waterproofing sheet comprises a polyethylene copolymer. The polyethylene copolymer has a molecular weight of 0.935 g / cm 3 Up to 0.945g / cm 3 The density and melt index of 1.0 g / 10 min to 1.5 g / 10 min. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to understand the above-mentioned features of the present invention in detail, a more specific description of the present invention briefly summarized above can be obtained by referring to some of the embodiments shown in the accompanying drawings. However, it should be noted that the accompanying drawings only illustrate typical embodiments of the present invention and are therefore not considered to be limiting of the scope of the present invention, because the present invention can be implemented with other equally effective embodiments.

[0020] Figure 1Shown are a series of gel permeation chromatograms of example resins and comparative resins according to at least one embodiment of the present disclosure.

[0021] Figure 2 is a graph showing viscosity flow curves at 190° C. of example resins and comparative resins according to at least one embodiment of the present disclosure.

[0022] Figure 3 is a graph showing Van GurpPalmen curves of example resins and comparative resins according to at least one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE INVENTION

[0023] Various embodiments and forms of the disclosed compounds, methods and articles will now be described, including specific embodiments and definitions adopted herein. Although specific embodiments are given in the following detailed description, it should be understood by those skilled in the art that these embodiments are merely exemplary and that the embodiments of the present disclosure may be practiced in other ways. Any reference to an embodiment may refer to one or more, but not necessarily all, of the compounds, methods or articles defined by the claims. The use of headers is merely for convenience and does not limit the scope of the present disclosure.

[0024] The present disclosure relates generally to polyethylene polymers and articles made therefrom, and more particularly to medium density polyethylene (MDPE) formed using, for example, metallocene catalysts. The MDPE described herein can be characterized as having a unique balance of chemical, physical, and mechanical properties relative to conventional MDPE, conventional LLDPE, and other conventional polyethylene grades. For example, the MDPE described herein exhibits a density traditionally associated with MDPE and HDPE while maintaining a small amount of long chain branching traditionally associated with LDPE (although to a lesser extent than encountered in LDPE). In addition, and compared to conventional LLDPE and other conventional polyethylene grades, the MDPE of the present disclosure can have a higher melt index, a higher viscosity at low shear rates, and improved processability, such as improved extrudability, while maintaining good bubble stability during the manufacturing process.

[0025] Articles made from such MDPE are also described. The MDPE described herein can be used in a variety of applications and articles, for example, laminated composite pipes, hygiene products, blown breathable films, waterproof sheets, and pipe adhesives, among others.

[0026] The MDPE described herein is a polyethylene copolymer. Compared to conventional LLDPE, the polyethylene copolymers of the present disclosure can maintain a small amount of long chain branching (also referred to as "LCB") in the copolymer, thereby providing reduced shrinkage and increased draft stability. The polyethylene copolymers of the present disclosure can exhibit a lower zero shear viscosity, resulting in lower motor torque and lower melt pressure and melt temperature during extrusion, thereby providing an increased output of the extruded polyethylene copolymer product. In addition, because the LCB is maintained, favorable processing properties are also maintained. A small amount of LCB can be demonstrated, for example, via a high melt index ratio and / or specific rheological properties, as shown in data obtained via a small angle oscillating shear (SAOS) experiment (e.g., η 0.01 / η 100 ratio, complex viscosity recorded at shear rates of 0.01 and 100 rad / s, respectively).

[0027] In addition, it has been found that the polyethylene copolymers of the present disclosure can provide excellent shear thinning properties with little or no melt fracture of the extrudate at high die shear rates. For example, a polyethylene copolymer having a low LCB with an MI of about 1 to about 2.5 g / 10 min and a MI of about 0.930 to about 0.945 g / cm 3 The polyethylene copolymers of the present disclosure having a combination of densities of 200 Å and 100 Å can provide blown films with excellent bubble stability (little or no melt fracture), which allows polymer processing aids (such as perfluoroalkanes or polyfluoroalkanes) to be optional in the blown films of the present disclosure. definition

[0028] As used herein, "olefins", or "olefins", are linear, branched or cyclic compounds of carbon and hydrogen having at least one double bond. For purposes of this specification and the claims thereto, when a polymer or copolymer is referred to as "comprising" an olefin, the olefin present in such polymer or copolymer is the polymerized form of the olefin. For example, when a copolymer is described as having an "ethylene" content of 35% to 55% by weight, it is understood that the monomer units in the copolymer are derived from ethylene in the polymerization reaction, and the derived units are present at 35% to 55% by weight, based on the weight of the copolymer.

[0029] As used herein, the terms "polyethylene polymer", "polyethylene", "ethylene polymer", "ethylene copolymer" and "ethylene-based polymer" refer to a polymer or copolymer comprising at least 50 mol% ethylene units, or at least 70 mol% ethylene units, or at least 80 mol% ethylene units, or at least 90 mol% ethylene units, or at least 95 mol% ethylene units, or 100 mol% ethylene units (in the case of a homopolymer).

[0030] As used herein, "polymer" may refer to homopolymers, copolymers, interpolymers, terpolymers, etc. A "polymer" has two or more monomer units that are the same or different. A "homopolymer" is a polymer having the same monomer units. A "copolymer" is a polymer having two or more monomer units that are different from each other.

[0031] As used herein, a "terpolymer" is a polymer having three monomeric units that are different from each other. The term "different" used in reference to monomeric units indicates that the monomeric units differ from each other in at least one atom or are isomerically different. Thus, the definition of copolymer as used herein includes terpolymers and the like. Likewise, the definition of polymer as used herein includes copolymers and the like.

[0032] As used herein, the 3 Ethylene polymers with a density of 0.910 to 0.925 g / cm 3 Ethylene polymers having a density of greater than 0.945 g / cm are referred to as "linear low density polyethylene" (LLDPE) when substantially linear (having little or no long chain branching), as is typically the case with Ziegler-Natta or metallocene-catalyzed PE, or branched low density polyethylene (LDPE) when significantly branched (having a high degree of long chain branching), as is typically the case with free radical polymerized PE; 3 Ethylene polymers with a density of 1000 Nm are called "high-density polyethylene" (HDPE).

[0033] Density was determined according to ASTM D 1505. Specimens were prepared according to ASTM D4703-Appendix 1, Procedure C, and then conditioned according to ASTM D618-Procedure A prior to testing.

[0034] As used herein and unless otherwise specified, the term "Cn" refers to hydrocarbon(s) containing n carbon atoms(s) per molecule, where n is a positive integer.

[0035] As used herein and unless otherwise specified, the term "hydrocarbon" refers to a class of compounds containing hydrogen bonded to carbon, and encompasses (i) saturated hydrocarbon compounds, (ii) unsaturated hydrocarbon compounds, and (iii) mixtures of hydrocarbon compounds (saturated or unsaturated), including mixtures of hydrocarbon compounds having different values ​​of n.

[0036] As used herein, the term "film" refers to a continuous, flat (in some cases, flexible) polymer structure having an average thickness ranging from 0.1 μm or 1 μm or 5 μm or 10 μm or 15 μm or 20 μm to 50 μm or 75 μm or 100 μm or 150 μm or 200 μm or 250 μm or 1000 μm or 2000 μm, or such a coating of similar thickness adhered to a flexible, non-flexible or another solid structure. A "film" can be made of or comprise a single layer or multiple layers. Each layer can be made of or contain a polyethylene copolymer of the present disclosure. For example, one or more layers of a "film" can include a mixture of a disclosed polyethylene copolymer and LDPE, LLDPE, another MDPE, HDPE, polypropylene, or a plastomer.

[0037] As used herein, a composition or film "free of" a component refers to a composition / film that is substantially free of the component or comprises the component in an amount of less than about 0.01 wt % based on the weight of the total composition.

[0038] As used herein, the term "polymerizable conditions" refers to conditions that favor the reaction of one or more olefin monomers to produce a polyolefin polymer when contacted with an activated olefin polymerization catalyst, and includes the skilled artisan's selection of temperature, pressure, reactant concentrations, optional solvents / diluents, reactant mixing / addition parameters, and other conditions within at least one polymerization reactor.

[0039] For simplicity, only some numerical ranges are clearly disclosed herein. However, a certain lower limit can be used in combination with any other upper limit to limit the scope that is not clearly recorded, similarly, a certain lower limit can be used in combination with any other lower limit to limit the scope that is not clearly recorded, and similarly, a certain upper limit can also be used in combination with any upper limit to limit the scope that is not clearly recorded. In addition, "in a range" or "in a range" includes each point or single value between its endpoints, even if there is no clear description, and includes the endpoint itself. Therefore, each point or single value itself can be used as a lower limit or upper limit in combination with other points or single values ​​or other lower or upper limits to limit the scope that is not clearly recorded.

[0040] The term "terminal olefin" refers to an olefin having a terminal carbon-carbon double bond in its structure ((R 1 R 2 )-C=CH2, where R 1 and R 2 can be independently hydrogen or any hydrocarbon group, for example R 1 is hydrogen, R 2 is an alkyl group). A "linear terminal olefin" is a terminal olefin as defined in this paragraph wherein R 1 is hydrogen, R 2 is hydrogen or a linear alkyl group.

[0041] The term "vinyl" refers to an olefin having the formula: wherein R is a hydrocarbon group, for example a saturated hydrocarbon group such as an alkyl group.

[0042] The term "vinylidene" refers to an olefin having the formula: Where R 1 and R 2 Each of is independently a hydrocarbon group, preferably a saturated hydrocarbon group such as an alkyl group.

[0043] The term "vinylene" or "1,2-di-substituted vinylene" refers to: (i) Olefins having the formula: or (ii) an olefin having the formula: or (iii) a mixture of (i) and (ii) in any proportion, Where R 1 and R 2 Each of is independently a hydrocarbon group, preferably a saturated hydrocarbon group such as an alkyl group.

[0044] The term "tri-substituted vinylidene" refers to an olefin having the formula: Where R 1 , R 2 and R 3 Each of is independently a hydrocarbon group, for example a saturated hydrocarbon group such as an alkyl group. Polyethylene copolymer

[0045] Embodiments of the present disclosure provide polyethylene copolymers such as MDPE. The MDPE described herein exhibits densities traditionally associated with conventional MDPE and conventional HDPE, while maintaining a small amount of long chain branching traditionally associated with LDPE (although to a lesser extent than seen in LDPE). The embodiments of the MDPE presented herein may also have a high melt index while additionally providing a higher viscosity at low shear rates, exhibiting benefits over conventional polyethylene grades. In addition, and relative to conventional polyethylene grades, the MDPE described herein may exhibit improved processability, such as improved extrudability, while maintaining good bubble stability during the blown film manufacturing process.

[0046] Thus, the polyethylene copolymers of various embodiments herein may exhibit one or more of the following properties: In the range of 0.930 to 0.945, for example, from 0.931, 0.932, 0.933, 0.934, 0.935, 0.936, 0.937 or 0.938 g / cm 3 The lower limit of any one of 0.945, 0.944, 0.943, 0.942, 0.941, 0.940, 0.939, 0.938 or 0.937 / cm 3 The upper limit of any one of the above, for example, 0.934 to 0.937 g / cm 3 , or 0.937 to 0.940 g / cm 3 , or 0.940 to 0.945 g / cm 3 , wherein any combination from the lower limit to any upper limit is considered (provided that the upper limit is greater than the lower limit), for example 0.934 to 0.945 g / cm 3 , 0.935 to 0.938 g / cm 3 or 0.935 to 0.937 g / cm 3 Density is determined according to ASTM D1505-19. A melt index (MI, also called I2 or I3 considering the 2.16 kg load used in the test) greater than 0.9 g / 10 min (ASTM D1238, 190°C, 2.16 kg) 2.16 ), for example, within the range of a lower limit of any one of 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, or 1.9 g / 10 min to an upper limit of any one of 2.5, 2.4, 2.3, 2.2, 2.1, 2, 1.9, 1.8, 1.7, or 1.6 g / 10 min, and ranges from any lower limit to any upper limit (provided that the upper limit is greater than the lower limit) are contemplated herein, for example, 0.9 to 2.5 g / 10 min, for example, 1 to 2 g / 10 min, for example, 1.1 to 1.3 g / 10 min, or 1.8 to 2 g / 10 min, but values ​​(or ranges) of MI are also contemplated. · A comonomer distribution reflecting similar comonomer incorporation levels on polymer chains of different lengths of a polyethylene copolymer, quantified as a composition distribution breadth index (CDBI). For example, polyethylene comonomers of various embodiments have a CDBI of 70% or more, such as 75% or more, such as 80% or more, 85% or more, or even 90% or more, although other values ​​(or ranges) of CBDI are contemplated. CDBI is defined as the weight percentage of copolymer molecules having a comonomer content within 50% of the median total molar comonomer content (i.e., within + / - 50% of the median, or in other words, within the range of 0.5x the median to 1.5x the median), and is cited, for example, in U.S. Pat. No. 5,382,630. In general, copolymers with a broader distribution result in a lower CDBI, whereas a theoretical copolymer having exactly the same relative comonomer content on all polymer chains of different lengths would have a CDBI of 100%. The CDBI of a copolymer is readily determined using techniques for isolating individual fractions of a copolymer sample. One such technique is to generate a solubility distribution curve using temperature rising elution fractionation (TREF), as described in WO1993003093 (which in turn refers to Wild et al., J. Poly. Sci., Poly. Phys. Ed., Vol. 20, p. 441 (1982) and U.S. Pat. No. 5,008,204 in this regard). All three of the aforementioned publications are incorporated herein by reference. Alternatively, a narrow comonomer distribution can be reflected in the T 75 -T 25 Value, where T 25 is the temperature at which 25% of the eluted polymer is obtained, and T 75 is the temperature at which 75% of the eluted polymer is obtained, both in a TREF experiment as described in US2019 / 0119413 (particularly in paragraphs

[0055] -

[0058] thereof, which description is incorporated herein by reference). The narrow distribution is reflected in T 75 -T 25 The difference in the value is less than 10°C, for example, in the range of 1 to 10°C, for example, 2 to 10°C, for example, from a lower limit of any one of 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5 or 6°C to an upper limit of any one of 10, 9.5, 9, 8.5, 8, 7.5, 7 or 6.5°C, for example, 1.5 to 4°C, 2 to 3.5°C, or 4 to 10°C, wherein combinations from any lower limit to any upper limit are considered (provided that the upper limit is greater than the lower limit), but other T values ​​are also considered. 75 -T 25 value.

[0047] Polyethylene copolymer can be the polymerization product of ethylene monomer and one or more olefin comonomers, for example alpha-olefin comonomer.Alpha-olefin comonomer can contain 3 to 12 carbon atoms, or 4 to 10 carbon atoms, or 4 to 8 carbon atoms.Olefin comonomer can be selected from propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 4-methylpent-1-ene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-hexadecene etc. and any combination thereof, such as 1-butene, 1-hexene and / or 1-octene.In some embodiments, polyene is used as comonomer. In some embodiments, polyene is selected from 1,3-hexadiene, 1,4-hexadiene, cyclopentadiene, dicyclopentadiene, 4-vinylcyclohex-1-ene, methyloctadiene, 1-methyl-1,6-octadiene, 7-methyl-1,6-octadiene, 1,5-cyclooctadiene, norbornadiene, ethylidene norbornene, 5-vinylidene-2-norbornene, 5-vinyl-2-norbornene and olefins formed in situ in the polymerization medium. In some embodiments, comonomers are selected from isoprene, styrene, butadiene, isobutylene, chloroprene, acrylonitrile and cycloolefins. In some embodiments, a combination of olefin comonomers is utilized. In some embodiments, olefin comonomers are selected from 1-butene and 1-hexene. The olefin comonomer content of the polyethylene copolymer can range from a lower limit of about 0.1 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt% or 8.5 wt% to an upper limit of about 20 wt%, 15 wt%, 13 wt%, 12.5 wt%, 12 wt%, 11.5 wt%, 11 wt%, 10.5 wt%, 10 wt%, 9.5 wt% or 9 wt%, based on the total weight of monomers in the polyethylene copolymer. The remainder of the polyethylene comonomer is made up of units derived from ethylene (e.g., from a lower limit of 80, 85, 88, 90, 91, 92, 92.5, 93, 93.5, or 94 weight percent to an upper limit of 90, 91, 92, 92.5, 93, 93.5, 94, 94.5, 95, 95.5, 96, 97, 99, or 99.9 weight percent). Ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 88 to 93 weight percent, such as 90 to 92.0 weight percent ethylene-derived units and the remainder olefin comonomer-derived content) are also contemplated herein.

[0048] The polyethylene copolymer may also have a high load melt index (HLMI) (also referred to as I HLMI in the case of a 21.6 kg load used in the identification test) ranging from a lower limit of 35, 40, 45, 50, or 55 g / 10 min to an upper limit of 80, 75, 70, 65, 60, or 55 g / 10 min.21 or I 21.6 ), wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are contemplated herein (e.g., 35 to 80 g / 10 min, or 45 to 70 g / 10 min, or 40 to 50 g / 10 min, or 55 to 65 g / 10 min, or 65 to 80 g / 10 min, or 70 to 80 g / 10 min). The term "high load melt index" ("HLMI") is the number of grams extruded in 10 minutes under a standard load (21.6 kg), and is inversely proportional to viscosity. As provided herein, HLMI (I 21 ) is measured according to ASTM D1238 (190°C / 21.6 kg) and is sometimes referred to as I 21 or I 21.6 .

[0049] The polyethylene copolymer may also have a melt index ratio (MIR, defined as I ) in the range of a lower limit of any of 25, 30, 35, 40, 45, 50, or 55 to an upper limit of any of 80, 75, 70, 65, 60, 55, or 50. 21.6 / I 2.16 ), wherein any lower limit to any upper limit is contemplated herein, such as within the range of any lower limit of 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, or 41 to an upper limit of 51, 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, or 40, wherein any lower limit to any upper limit is contemplated herein (e.g., 35 to 45, 37 to 44, 37 to 40, or 40 to 44). MIR is 1 21 / I2 ratio.

[0050] The polyethylene copolymer may also have a molecular weight distribution (MWD) of 2 to 8. The MWD may also be in a range of 2, 2.5, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, or a lower limit of 4 to 3.5, 3.6, 3.7, 3.8, 3.9, 4, 4.1, 4.2, 4.3, 4.4, 4.5, 5, 6, or an upper limit of 8, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are contemplated as long as the upper limit of the range is greater than the lower limit, e.g., 2 to 5, or 3 to 6, or 3.5 to 5, or 4 to 4.5. The MWD is defined as the weight average molecular weight (Mw) divided by the number average molecular weight (Mn), (Mw / Mn).

[0051] The weight average molecular weight (Mw) of the polyethylene copolymers of various embodiments can range from 70,000 to 90,000 g / mol, such as 75,000 to 85,000 g / mol, such as 75,000 to 80,000 g / mol, or 80,000 to 85,000 g / mol, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are contemplated.

[0052] The number average molecular weight (Mn) of the polyethylene copolymers of various embodiments can range from 15,000 to 30,000 g / mol, such as 15,000 to 25,000 g / mol, or 17,000 to 21,000 g / mol, or 18,000 to 20,000 g / mol, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are contemplated.

[0053] The Z-average molecular weight (Mz) of the polyethylene copolymers of various embodiments can be in the range of 150,000 to 210,000 g / mol, such as 155,000 to 205,000 g / mol, 160,000 to 200,000 g / mol, such as 165,000 to 195,000 g / mol, 170,000 to 190,000 g / mol, or 175,000 to 185,000 g / mol, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are contemplated (e.g., 190,000 to 205,000 g / mol, or 180,000 to 185,000 g / mol, or 165,000 to 175,000 g / mol, or 165,000 to 170,000 g / mol).

[0054] The polyethylene copolymers of various embodiments may also exhibit a small amount (but non-zero) of long chain branching. As previously described, this can be determined, for example, via SAOS viscosity data (particularly η 0.01 / η 100 ) and / or MIR. In addition, the LCB index (g' or alternatively g'vis) can be less than 1, such as in the range of 0.9 to 0.99 or 0.96 to 0.985, although the index is still significantly higher than the g' value of high-LCB polyethylene (such as LDPE prepared by free radical polymerization).

[0055] Another useful parameter for indicating the presence of LCB is Figure 3 In particular, a polyethylene copolymer (even an LLDPE) having some LCB will show an inflection point in its Van Gurp Palmen curve, whereas an LLDPE without any LCB (e.g., Figure 3 Comparative resin 3) does not show such an inflection point.

[0056] The distribution and moment of molecular weight (Mw, Mn, Mw / Mn, etc.), and branching index (g'vis) were determined by using high temperature gel permeation chromatography (Polymer Char GPC-IR), which was equipped with a multi-channel bandpass filter-based infrared detector IR5, an 18-angle Wyatt Dawn Heleos light scattering detector, and a 4-capillary viscometer with a Wheatstone bridge configuration. Three Agilent PLgel 10μm mixed-B LS columns were used to provide polymer separation. Aldrich reagent grade 1,2,4-trichlorobenzene (TCB) containing 300ppm antioxidant butylated hydroxytoluene (BHT) was used as the mobile phase. The TCB mixture was filtered through a 0.1μm Teflon filter and degassed with an online degasser before entering the GPC instrument. The nominal flow rate was 1.0ml / min and the nominal injection volume was 200μL. The entire system including the transfer line, column, and viscometer detector was loaded in an oven maintained at 145°C. The polymer sample was weighed and sealed in a standard vial, to which 80 μL of a mobile marker (heptane) was added. After the vial was loaded into the autosampler, the polymer was automatically dissolved in the instrument with 8 mL of added TCB solvent. The polymer was dissolved at 160° C. with continuous shaking for about 2 hours. The concentration (c) of each point in the chromatogram was calculated from the IR5 broadband signal intensity (I) minus the baseline using the following equation: c=βI, where β is the mass constant.

[0057] The mass recovery is calculated from the ratio of the integrated area of ​​the concentration chromatogram to the elution volume and the injected mass is equal to the predicted concentration multiplied by the injection loop volume. The conventional molecular weight (IR MW) is determined by combining the universal calibration relationship with a column calibration performed with a series of monodisperse polystyrene (PS) standards ranging from 700 to 10 million g / mol. The MW at each elution volume is calculated using the following equation: The variables with the subscript "PS" represent polystyrene, while those without a subscript are test samples. PS =0.67 and K PS=0.000175, while a and K are a and K calculated from empirical equations (Sun, T. et al. Macromolecules 2001, 34, 6812) for ethylene-hexene copolymers, where a = 0.695 and K = 0.000579 (1-0.75 Wt), where Wt is the weight fraction of the hexane comonomer. It should be noted that the comonomer composition is determined by the ratio of the IR5 detector intensities corresponding to the CH2 and CH3 channels calibrated with a series of PE and ethylene-hexene homo / copolymer standard samples, the nominal values ​​of which are previously determined by NMR or FTIR. Here, the concentration is expressed in g / cm 3 The molecular weight is expressed in g / mol and the intrinsic viscosity (and therefore K in the Mark-Houwink equation) is expressed in dL / g.

[0058] The LS molecular weight (M) at each point in the chromatogram was determined by analyzing the LS output using the Zimm model of static light scattering. Here, ΔR(θ) is the excess Rayleigh scattering intensity measured at the scattering angle θ, c is the polymer concentration determined by IR5 analysis, A2 is the second virial coefficient, p(θ) is the shape factor of the monodisperse random coils, and Ko is the optical constant of the system: Where N A is Avogadro's constant and (dn / dc) is the refractive index increment of the system. The refractive index of TCB at 145°C and λ=665nm is n=1.500. For purposes of this disclosure and the claims thereto, for ethylene-hexene copolymers, (dn / dc)=0.1048.

[0059] The specific viscosity is determined using a high temperature polymer Char viscometer with four capillaries arranged in a Wheatstone bridge configuration and two pressure sensors. One sensor measures the total pressure drop across the detector and the other, located between the two sides of the bridge, measures the differential pressure. The specific viscosity η of the solution flowing through the viscometer is s Calculated from its output. The intrinsic viscosity [η] at each point in the chromatogram avg From the equation [η] = η S / c is calculated where c is the concentration and is determined from the IR5 broadband channel output.

[0060] Branching index (g' vis ) is calculated using the output of the GPC-IR5-LS-VIS method as follows. The average intrinsic viscosity of the sample [η] avg Calculated by the following formula: wherein the sum is taken from all chromatogram slices i between the integration limits. Branching index g' vis Defined as: Among them, M v is the viscosity average molecular weight based on molecular weight determined by LS analysis, and K and α are the K and α of a benchmark linear polymer, and for purposes of this disclosure, α and K are the same as described above for linear polyethylene polymers.

[0061] In addition, the polyethylene copolymer can have a range of 8,000 to 25,000 Pa·s, such as from the lower limit of any one of 8,000, 9,000, 10,000, 11,000, 12,000, 13,000, 14,000, 15,000 or 16,000 Pa·s to 25,000, 24,000, 23,000, 24,000, 25,000, 26,000, 27,000, 28,000, 29,000, 30,000, 31,000, 32,000, 33,000, 34,000, 36,000, 37,000, 38,000, 39,000, 40,000, 41,000, 42,000, 43,000, 44,000, 45,000, 46,000, 47,000, 48,000, 49,000, 50,000, 51,000, 52,000, 53,000, 54,000, 56,000, 57,000, 58,000 A complex shear viscosity (η*) at 0.01 rad / s and 190° C. with an upper limit of any one of 23,000, 21,000, 20,000, 19,000, 18,000, 17,000, or 16,000 Pa·s, wherein ranges from any lower limit to any upper limit are contemplated (e.g., 8,000 to 10,000 Pa·s or 15,000 to 25,000 Pa·s).

[0062] The complex shear viscosity (η*) at 100 rad / s and 190°C can be in the range of 900 to 1,500 Pa·s, for example, from a lower limit of any one of 900, 1,000, 1,100 or 1,200 Pa·s to an upper limit of any one of 1,500, 1,400, 1,300, 1,200 or 1,100 Pa·s, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 900 to 1,100 Pa·s or 1,100 to 1,300 Pa·s) are also contemplated.

[0063] In some embodiments, the polyethylene copolymer has a shear thinning ratio (η*@0.01 / 100) less than 20, or in the range of 5 to 20, such as from a lower limit of any one of 7, 8, 9, 10, 11, 12, 13 or 14 to an upper limit of any one of 20, 19, 18, 17, 16, 15, 14 or 13, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 8 to 10, or 12 to 13, or 17 to 19) are also contemplated.

[0064] Rheological data such as "complex shear viscosity (η*)", reported in Pascal-seconds, can be measured at 0.01 rad / s and 100 rad / s. Complex shear viscosity and other rheological measurements can be obtained from small angle oscillatory shear (SAOS) experiments.

[0065] For example, complex shear viscosity can be measured in dynamic mode using parallel plates (diameter = 25 mm) with a rotational rheometer such as Advanced Rheometrics ExpansionSystem (ARES-G2 model) or Discovery Hybrid Rheometer (DHR-3 model) under a nitrogen atmosphere. The rheometer can be thermally stabilized at 190°C for at least 20 minutes before the compression molded specimen is inserted onto the parallel plates. In order to determine the viscoelastic behavior of the specimen, a frequency sweep in the range of 0.01 to 628 rad / s can be performed at a temperature of 190°C at a constant strain that does not affect the measured viscoelasticity. The scanning frequency is equally spaced on a logarithmic scale so that 5 frequencies are detected per decade. Depending on the molecular weight and temperature, a strain of 3% can be used, and the linearity of the response is verified. A nitrogen stream is circulated through the oven to minimize chain extension or crosslinking during the experiment. The sample can be compression molded at 190°C without a stabilizer. A sinusoidal shear strain can be applied. The shear thinning slope (STS) can be measured by plotting the logarithm (base 10) of the dynamic viscosity against the logarithm (base 10) of the frequency. The slope is 100s -1 log(dynamic viscosity) at a frequency of 0.01s -1 The difference in log(dynamic viscosity) at the frequency of the complex shear viscosity (η*) is divided by 4. The Carreau-Yasuda model can be used to fit the complex shear viscosity (η*) versus frequency (ω): η*-η∞=(η0-η∞)*(1+(λω) a ) (n-1) / a. .

[0066] The five parameters in this model are: η0, zero shear viscosity; λ, relaxation time; n, power law exponent; η∞, infinite rate viscosity; a, transition exponent. While the dynamic viscosity is independent of frequency, the zero shear viscosity is the value at the plateau in the Newtonian region of the flow curve at low frequencies. The relaxation time corresponds to the inverse of the frequency at which shear thinning begins. The power law exponent describes the degree of shear thinning, since the magnitude of the slope of the flow curve at high frequencies approaches n-1 on a log(η*)-log(ω) plot. For Newtonian fluids, n=1, and the kinematic complex viscosity is independent of frequency.

[0067] In addition to dynamic viscosity and complex viscosity (each in Pascal seconds), various other parameters are collected at each frequency scan in the SAOS experiment, including storage modulus (Pa), loss modulus (Pa), complex modulus (Pa), tan (δ) and phase angle. Phase angle is plotted against complex shear modulus from rheological experiments to produce Van Gurp Palmen plots, which can be used to extract some information about molecular features, such as linear versus long chain branching chains, long chain branching types, polydispersity (Dealy, MJ, Larson, RG, "Structure and Rheology of Melted Polymers", Carl Hanser Verlag, Munich 182-183 (2006)). It is also shown that Van Gurp Palmen plots can be used to reveal the presence of long chain branching in polyethylene. See Trinkle, S., Walter, P., Friedrich, C., "Van Gurp-Palmen Plot II-Classification of long chain branched polymers by their topology", in 41 Rheol. Acta 103-113 (2002).

[0068] The "shear thinning ratio" (reported as a unitless number) is characterized by a decrease in complex viscosity with increasing shear rate. Herein, shear thinning can be determined as the ratio of the complex viscosity at a frequency of 0.01 rad / s to the complex viscosity at a frequency of 100 rad / s.

[0069] Furthermore, the balance of some of the advantageous properties of the polyethylene copolymers of the present disclosure can be represented by one or more overall properties, such as an "alpha parameter," a "beta parameter," or a combination thereof.

[0070] The α parameter is expressed by Equation 1: α parameter = (MIR*η 0.01 / η 100 )*(T 75 -T 25 ) / MWD (Equation 1)

[0071] The β parameter is expressed by Equation 2: β parameter = (MIR*η 0.01 / η 100 )*((T 75 -T 25 ) / MWD) 2 (Equation 2)

[0072] In Equations 1 and 2, MIR is the melt index ratio, η0.01 is the complex shear viscosity (η*) at 0.01 rad / s and 190°C, η 100 is the complex shear viscosity (η*) at 100 rad / s and 190°C, T 75 -T 25 It is T 75 -T 25 Value, where T 25 is the temperature at which 25% of the eluted polymer is obtained, T 75 is the temperature at which 75% of the eluted polymer is obtained (determined by TREF, as cited above) and MWD is the molecular weight distribution.

[0073] The polyethylene copolymers of various embodiments of the present disclosure have an alpha parameter (Equation 1) of 230 to 1,000, such as 240 to 500, such as 240 to 300, or 240 to 250, or 290 to 330, or 440 to 500, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are also contemplated. In general, the alpha parameter shows a strong dependence on long chain branching, and thus the alpha parameter captures the uniqueness of the combination of these properties exhibited in the polyethylene copolymers of the present disclosure.

[0074] The polyethylene copolymers of the present disclosure may have a β parameter (Equation 2) of 120 to 400, such as 150 to 350, such as 170 to 200, or 190 to 230, or 260 to 310, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits are also contemplated. In general, the β parameter shows a strong dependence on the breadth of the comonomer distribution (via T 75 -T 25 Term), and thus the β parameter captures the uniqueness of the combination of these properties exhibited in the polyethylene copolymers of the present disclosure.

[0075] The polyethylene copolymer can have a vinylidene content of 0.05 to 0.1 vinylidene groups / 1000 carbon atoms, such as 0.06 to 0.09 vinylidene groups / 1000 carbon atoms, such as 0.07 to 0.08 vinylidene groups / 1000 carbon atoms, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 0.07 to 0.1 vinylidene groups / 1000 carbon atoms or 0.08 to 0.09 vinylidene groups / 1000 carbon atoms) are also contemplated.

[0076] The polyethylene copolymer can have a trisubstituted vinylidene content of 0.03 to 0.15 trisubstituted vinylidene groups / 1000 carbon atoms, such as 0.09 to 0.15 trisubstituted vinylidene groups / 1000 carbon atoms, such as 0.1 to 0.15 trisubstituted vinylidene groups / 1000 carbon atoms, or 0.09 to 0.1 trisubstituted vinylidene groups / 1000 carbon atoms, or 0.1 to 0.12 trisubstituted vinylidene groups / 1000 carbon atoms, or 0.12 to 0.14 trisubstituted vinylidene groups / 1000 carbon atoms, wherein ranges from any of the foregoing lower limits to any of the foregoing upper limits (e.g., 0.09 to 0.12 trisubstituted vinylidene groups / 1000 carbon atoms) are also contemplated.

[0077] The polyethylene copolymer can have a vinyl content of 0.01 to 0.02 vinyl groups / 1000 carbon atoms, such as 0.012 to 0.018 vinyl groups / 1000 carbon atoms, such as 0.014 to 0.016 vinyl groups / 1000 carbon atoms, wherein ranges from any foregoing lower limit to any foregoing upper limit are also contemplated.

[0078] In some embodiments, the polyethylene copolymer has a vinylidene content of 0.005 vinylidene groups / 1000 carbon atoms or less, such as 0 vinylidene groups / 1000 carbon atoms.

[0079] The polyethylene copolymer can have a total unsaturated portion of 0.1 to 0.25, such as 0.17 to 0.23, such as a lower limit of any one of 0.17, 0.18, 0.19 or 0.20 to an upper limit of any one of 0.23, 0.22, 0.21 or 0.20, wherein any lower limit to any upper limit range (e.g., 0.17 to 0.22, or 0.18 to 0.2, or 0.21 to 0.23) is considered. The total unsaturated portion is the sum of vinylidene / 1000 carbon atoms, trisubstituted vinylidene (olefin) / 1000 carbon atoms, vinyl / 1000 carbon atoms, and vinylidene / 1000 carbon atoms.

[0080] You can use a 600MHz or higher 1 The H frequency spectrometer was collected at 120 °C in a 10 mm probe. 1HNMR data. Data can be recorded using a maximum pulse width of 45°, 5 seconds between pulses, and an average of 512 transient signals. The spectrum signal is integrated. The polyethylene copolymer sample can be dissolved in deuterated 1,1,2,2,-tetrachloroethane-d2 at a concentration of 30 mg / ml and then inserted into the spectrograph magnet. Prior to data analysis, the spectrum can be calibrated by setting the residual hydrogen-containing solvent resonance to 5.98 ppm. Disubstituted vinylidene can be measured as the number of vinylidene groups / 1,000 carbon atoms using the resonance between 5.55-5.31 ppm. Trisubstituted vinylidene ("trisubstituted") end groups can be measured as the number of trisubstituted groups / 1,000 carbon atoms using the resonance between 5.3-5.11 ppm by the difference with vinyl. Vinyl end groups can be measured as the number of vinyl groups / 1,000 carbon atoms using the resonance between 5.10-4.95 and 5.3-4.85 ppm. Vinylidene end groups can be measured as the number of vinylidene groups per 1,000 carbon atoms using the resonance between 4.84-4.70 ppm.

[0081] As used herein, a "triad" is three monomer repeat units: for example, AAA, AAB, BAA, BAB, ABA, BBA, ABB, BBB added and normalized to 1. A = CH2; B = C6. By 13 C-NMR triad analysis provides insight into the sequence distribution and blockiness of the material. In some embodiments, the polyethylene copolymer has an [EEE] triad content of 95 to 99 mol%, such as 95 to 98 mol%, such as 95.5 to 97.5 mol%, such as 96 to 97 mol%, such as 96 to 96.5 mol% or 96.5 to 97 mol%, wherein any lower limit to any upper limit range (e.g., 97 to 97.5 mol%) is contemplated, such as by 13 C NMR ( 13 C NMR). ("E" is ethylene). In some embodiments, the polyethylene copolymer has a [HEE] triad content of 1.4 to 2.5 mol%, such as 1.5 to 2.5 mol% or 1.4 to 2.2 mol%, such as 1.7 to 2.2 mol%, such as 1.7 to 1.8 mol%, or 1.8 to 2.1 mol%, or 2 to 2.1 mol%, wherein ranges from any lower limit to any upper limit are contemplated, such as by 13 C NMR measurement) ("H" is hexene and "E" is ethylene).

[0082] In some embodiments, the polyethylene copolymer has 0.7 to 1 mol%, such as 0.8 to 1 mol%, such as 0.8 to 0.9 mol% or 0.9 to 1 mol% of 13In some embodiments, the polyethylene copolymer has 0.0 mol% to 0.1 mol%, such as less than 0.1 mol% or less than 0.05 mol%, or less than 0.01 mol% of [EHE] triad content determined by C NMR. 13 In some embodiments, the polyethylene copolymer has less than 0.05 mol% of [HHH] triad content as determined by C NMR. 13 In some embodiments, the polyethylene copolymer has less than 0.05 mol% of [HEH] triad content as determined by C NMR. 13 [EHH] triad content determined by C NMR.

[0083] for 13 C NMR, the sample can be dissolved in deuterated 1,1,2,2-tetrachloroethane-d2 (tce-d2) at a concentration of 67 mg / mL at 140°C. The spectrum can be recorded at 120°C using a Bruker NMR spectrometer of at least 600 MHz with a 10 mm cryoprobe. 90° pulses, 10 s delay, 512 transients, and gated decoupling can be used to measure 13 C NMR. The polymer resonance peaks are referenced to the polyethylene major peak at 29.98 ppm. Randall describes chemical shift assignments for vinyl copolymers in "A Review Of High Resolution Liquid Carbon Nuclear Magnetic Resonance Characterization of Ethylene-Based Polymers", Polymer Reviews, 29: 2, 201-5 317 (1989). Copolymer content, mole % and weight %, triad sequence and diad calculations are also calculated and described in this article by the method established by Randall. Olefins from waste processing

[0084] The processing of waste materials (such as waste plastics) can lead to the production or recovery of olefins, or attribute the waste raw materials to olefins used to make the polymer compositions disclosed herein (e.g., polyethylene copolymers), including any alpha-olefins disclosed herein. Waste materials can include waste plastics obtained from any source, including but not limited to urban, industrial, commercial or consumer sources. Waste plastics can also be obtained from a common source or from a mixed source, including mixed waste plastics obtained from urban or regional sources and / or from waste streams of polyethylene terephthalate (PET), HDPE, MDPE, LDPE, LLDPE, polypropylene and / or polystyrene. In addition, waste materials can include thermoplastic elastomers and thermosetting rubbers, such as from tires and other products made of natural rubber, polybutadiene, styrene-butadiene, butyl rubber and EPDM.

[0085] Processed waste may also include any of a variety of used polymeric and non-polymeric articles, but is not limited thereto. Some examples of many types of polymeric articles may include: films (including cast, blow molded, etc.), sheets, fibers, woven and non-woven fabrics, furniture (e.g., garden furniture), sports equipment, bottles, food and / or liquid storage containers, transparent and translucent articles, toys, pipes and tubes, sheets, packaging, bags, bags, coatings, caps, closures, crates, pallets, cups, non-food containers, barrels, insulators, and / or medical devices. Additional examples include automotive, aviation, marine and / or boat components (e.g., bumpers, grilles, decorative parts, dashboards, instrument panels, etc.), wire and cable sheathing, agricultural films, geomembranes, playground equipment, and other such articles, whether blow molded, rotomolded, injection molded, etc. Any of the foregoing may include a mixture of polymeric and non-polymeric articles (e.g., packaging or other articles may include inks, paperboard, paper, metal deposits, etc.). One of ordinary skill will appreciate that such polymeric articles can be made from any of a variety of polymeric and / or non-polymeric materials, and that the polymeric materials can vary widely (e.g., vinyl, propylene, butyl polymers, and / or any C2 to C3 based polymers). 40 or even higher olefins, and also include polymers based on any one or more types of monomers, such as C2 to C 40 Typical examples include ethylene, propylene, butene, pentene, hexene, heptene, and octene; and polyolefin (including cycloolefin) monomers such as ethylidene norbornene (ENB) and vinylidene norbornene (VNB) (including, for example, when such cycloolefins are used as comonomers, such as with ethylene monomers).

[0086] Processing of waste materials, such as via pyrolysis of waste plastics, can directly produce or recover olefins for the preparation of such polymer compositions, or via use of the waste materials as feed to the system, such as by accounting for, allocating and / or offsetting or replacing other hydrocarbons in the mass or energy balance of the system, as determined, for example, according to a third party certification related to circularity. A polymer whose circularity is certified by a third party certification may be referred to as certified circular. An example of such a certification is the mass balance chain of custody approach proposed by International Sustainability and Carbon Certification.

[0087] Various methods may be employed to produce, recover, or attribute olefins for use in the polymers disclosed herein. For example, olefins may be obtained from or associated with co-processing of waste materials (e.g., waste plastics) with other hydrocarbon feeds in cracking, coking, hydrotreating, and / or pyrolysis processes. For example, olefins may be directly or indirectly obtained from a fluid catalytic cracking unit, a delayed coking unit, a fluid coking unit (including a FLEXICOKING TM Units), hydroprocessing units (including hydrocracking and hydroprocessing units) and / or steam cracking units (including gas or liquid steam cracking units) that receive such waste as feed or co-feed. Alternatively, such a unit may receive a pyrolysis product (e.g., separated or combined recycled pyrolysis gas and / or recycled pyrolysis oil) of processing such waste as feed or co-feed. Olefins may be produced directly by this method, or may be obtained by further processing, such as separation, treatment and / or cracking of the effluent of this method. As an example, olefins may be obtained by processing recycled pyrolysis oil and / or recycled pyrolysis gas produced by pyrolysis of waste plastics. "Recycled pyrolysis oil" as used herein refers to a material composition that is liquid when measured at 25°C and 1atm, and at least a portion of which is obtained from the pyrolysis of recycled waste (e.g., recycled waste plastic). "Recycled pyrolysis gas" as used herein refers to a material composition that is gaseous at 25°C and 1atm, and at least a portion of which is obtained from the pyrolysis of recycled waste. In addition, waste materials (such as waste plastics) are co-processed as feed or co-feed to fluid catalytic cracking units, delayed coking units, fluid coking units (including FLEXICOKING TM units), hydroprocessing units (including hydrocracking and hydrotreating units) and / or steam cracking units (including gas or liquid steam cracking units) can result in waste being attributed to the olefins, polymers or polymer compositions described herein, for example, as determined by accounting for, allocating and / or offsetting or replacing other hydrocarbons in the mass or energy balance of the system, for example based on a third party certification related to circularity.

[0088] Therefore, the method according to various embodiments of this article may further include obtaining olefins produced or recovered from the processing of waste plastics or olefins attributed to the processing of waste plastics, for example, for use in polymerization methods as described elsewhere herein; and the polymer compositions of various embodiments described herein (e.g., polyethylene copolymers) may include olefins produced or recovered from the processing of waste plastics or olefins attributed to the processing of waste plastics. As an example, at least a portion of the olefin content (e.g., for use in methods as described herein and / or included in compositions as described herein) can come from olefins directly produced or recovered from the processing of waste plastics. Similarly, the processing of waste plastics can be attributed to at least a portion of olefins (e.g., for use in methods as described herein and / or included in compositions as described herein). Blends and Additives

[0089] In some embodiments, the polyethylene copolymers described herein can be formulated (e.g., blended) with one or more other polymer components. In some embodiments, those other polymer components are alpha-olefin polymers, such as polypropylene or polyethylene homopolymers and copolymer compositions. In some embodiments, those other polyethylene polymers are selected from: LLDPE, HDPE, MDPE, LDPE, and other differentiated polyethylenes.

[0090] In some embodiments, the blend of preparation may contain additives, which are determined based on the final use of the blend of preparation. In some embodiments, the additive is selected from fillers, antioxidants, phosphites, anti-adhesion additives, tackifiers, UV stabilizers, heat stabilizers, anti-blocking agents, mold release agents, antistatic agents, pigments, colorants, dyes, waxes, silicon oxides, processing aids, neutralizers, lubricants, surfactants and nucleating agents. In some embodiments, the additive is present in an amount of 0.1ppm to 5.0% by weight.

[0091] The polyethylene copolymers of the present disclosure may optionally be blended with one or more processing aids to form polyethylene blends. Due to the improved properties of the polyethylene copolymers of the present disclosure, advantageously, such processing aids may be omitted even in blown films (e.g., films of some embodiments, particularly blown films, may be free of or substantially free of polymer processing aids, particularly fluorine-containing polymer processing aids, wherein "substantially free of" means free of any intentionally added components, but allowing up to 100 ppm of such components (one or more) as impurities). Aggregation methods

[0092] The polymerization process may include gas phase polymerization, particularly fluidized bed gas phase polymerization. Gas phase polymerization may be carried out in any suitable reactor system, such as a stirred or paddle type reactor system. See U.S. Pat. Nos. 7,915,357; 8,129,484; 7,202,313; 6,833,417; 6,841,630; 6,989,344; 7,504,463; 7,563,851; 8,101,691 and 9,718,896 for a discussion of suitable gas phase fluidized bed polymerization systems, which are well known in the art. Each of these references is incorporated herein by reference in its entirety.

[0093] In such a polymerization process, a gas phase fluidized bed process is carried out by continuously passing a stream containing ethylene and olefin comonomers through a fluidized bed reactor under reaction conditions and in the presence of a catalyst composition at a speed sufficient to keep a bed of solid particles in suspension. A stream containing unreacted ethylene and olefin comonomers (which may be referred to as a "cycle gas" stream) is continuously taken out of the reactor, compressed, cooled, optionally partially or completely condensed, and recycled back to the reactor. The prepared polyethylene copolymer is taken out of the reactor, and replacement ethylene and olefin comonomers are added to the recycle stream. In some embodiments, a gas inert to the catalyst composition and reactants is present in the gas stream.

[0094] The circulating gas may include an induced condensing agent (ICA). ICA is one or more non-reactive alkanes that are condensable to remove heat of reaction during the polymerization process. In some embodiments, the non-reactive alkanes are selected from C1-C6 alkanes, such as one or more of propane, butane, isobutane, pentane, isopentane, hexane and isomers and derivatives thereof. In some cases, a mixture of two or more such ICAs may be particularly desirable (e.g., propane and pentane, propane and butane, butane and pentane, etc.).

[0095] Various gas phase polymerization methods can be used. For example, the polymerization can be carried out in a "dry" mode (or uncondensed mode), a "condensed" mode, or a "supercondensed" mode.

[0096] In the "dry" mode (typical ICA concentrations are less than 10 mol% relative to the total cycle gas), ICA is injected into the reactor along with the other components of the cycle gas in gaseous form. In the "condensed" or "supercondensed mode", ICA (typical ICA concentrations can be as high as 30-35% relative to the total cycle gas) is in liquid form mixed with the other components of the cycle gas. In some embodiments, the gas phase process is substantially free of ICA. It may be desirable to maximize the ICA concentration to achieve faster commercial run times; however, reducing ICA can have a beneficial effect on comonomer distribution.

[0097] The reactor pressure can be 100 psig (680 kPag) to 500 psig (3448 kPag), or 200 psig (1379 kPag) to 400 psig (2759 kPag), or 250 psig (1724 kPag) to 350 psig (2414 kPag). In some embodiments, the reactor is operated at a temperature of 60°C to 120°C, 60°C to 115°C, 70°C to 110°C, 70°C to 95°C, or 80°C to 90°C. The ratio of hydrogen to ethylene can be 10 to 30 ppm / mol%, such as 15 to 25 ppm / mol%, such as 16 to 20 ppm / mol%.

[0098] The mole % of ethylene can be 25.0-90.0 mole %, or 50.0-90.0 mole %, or 70.0-85.0 mole %, and the ethylene partial pressure is in the range of 75 psia (517 kPa) to 300 psia (2,069 kPa), or 100 to 275 psia (689 to 1,894 kPa), or 150 to 265 psia (1,034 to 1,826 kPa), or 180 to 200 psia (1,241 to 1,379 kPa).

[0099] The ethylene concentration in the reactor may also be in the range of 35 to 95 mol%, such as in the range of a lower limit of 35, 40, 45, 50 or 55 mol% to an upper limit of 70, 75, 80, 85, 90 or 95 mol%, and further wherein the ethylene mol% is measured based on the total moles of gas in the reactor (including (if present) ethylene and / or comonomer gas and inert gases such as nitrogen, isopentane or other ICA(s) and the like); as with the vol-ppm hydrogen, for convenience this measurement may be made at the recycle gas outlet rather than in the reactor itself. The comonomer concentration may be in the range of 0.2 to 1.0 mol%, such as in the range of a lower limit of 0.2, 0.3, 0.4 or 0.5 mol% to an upper limit of 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95 or 1.0 mol%. catalyst

[0100] The catalyst used in the polymerization can be a metallocene catalyst. In particular, the metallocene catalyst can be selected from the catalyst described in Patent Cooperation Treaty Publication Nos. WO1993008221, WO1996008520, WO1998044011 and WO2007130277, which are incorporated herein by reference for all purposes. For example, the catalyst can be a silicon oxide supported metallocene catalyst prepared from a composition comprising dichloro dimethylsilyl bis (tetrahydroindenyl) zirconium metallocene and methylaluminoxane cocatalyst. In some embodiments, the catalyst is dichloro dimethylsilyl bis (tetrahydroindenyl) zirconium. Products

[0101] Embodiments of the present disclosure also generally relate to articles. The polyethylene copolymers of the present disclosure may be particularly suitable for making end-use articles, such as films (e.g., such as may be formed by lamination, extrusion, coextrusion, casting and / or blow molding); and other articles that may be formed, for example, by rotational molding or injection molding. Other articles that may be made from the polyethylene copolymers of the present disclosure may include, but are not limited to, laminated composite pipes, sanitary products, waterproof sheets (e.g., pre-laid waterproof sheets), and pipe adhesives.

[0102] Illustrative but non-limiting examples of hygienic articles that can be prepared using the polyethylene copolymer(s) described herein include blown breathable films.

[0103] The polyethylene copolymers may be formed into articles by any suitable method, such as cast film extrusion, blown film extrusion, rotational molding, injection molding, or other suitable methods. In some embodiments, the polyethylene copolymers may be used in blends.

[0104] The polyethylene copolymers of the present disclosure can provide excellent shear thinning properties, with little or no melt fracture of the extrudate at high die shear rates. For example, the polyethylene copolymers of the present disclosure (e.g., having an MI of about 1 to about 2.5 g / 10 min and an MI of about 0.930 to 0.945 g / cm 3 The polyethylene copolymers of the present invention (e.g., having a MI of about 1 to about 2.5 g / 10 min and a MI of about 0.930 to 0.945 g / cm2) can be used as a skin layer in a blown film to provide a film without melt fracture, which allows polymer processing aids (e.g., perfluoroalkanes or polyfluoroalkanes) to be only optional (or preferably, completely eliminated from such blown film formulations so that the film is free of or substantially free of polymer processing aids, such as fluoropolymer processing aids). In addition, compared to conventional LLDPE, conventional MDPE, and other conventional polyethylene copolymers, the polyethylene copolymers of the present invention (e.g., having a MI of about 1 to about 2.5 g / 10 min and a MI of about 0.930 to 0.945 g / cm2) can be used as a skin layer in a blown film to provide a film without melt fracture, which allows polymer processing aids (e.g., perfluoroalkanes or polyfluoroalkanes) to be only optional (or preferably, completely eliminated from such blown film formulations so that the film is free of or substantially free of polymer processing aids, such as fluoropolymer processing aids). 3 density) can provide films formed with reduced motor load and melt pressure (which increases input) due to improved flow behavior.

[0105] In some embodiments, the laminated composite pipe includes the polyethylene copolymer of the present disclosure. In at least one embodiment, the polyethylene copolymer suitable for the laminated composite pipe may have one or more of the following properties: a complex shear viscosity (η*) of 15,000 Pa·s to 25,000 Pa·s at 0.01 rad / s and 190°C; a complex shear viscosity (η*) of 1,100 Pa·s to 1,300 Pa·s at 100 rad / s and 190°C; a viscosity of 0.935 g / cm 3 Up to 0.942g / cm 3 and a melt index of 1 g / 10 min to 1.5 g / 10 min. Other properties of polyethylene copolymers suitable for laminated composite pipes are also considered.

[0106] In some embodiments, the pre-laid waterproof sheet includes the polyethylene copolymer of the present disclosure. In at least one embodiment, the polyethylene copolymer suitable for the pre-laid waterproof sheet may have one or more of the following properties: 0.935 g / cm 3 Up to 0.945g / cm 3 The density of 1.0 g / 10 min and the melt index of 1.0 g / 10 min to 1.5 g / 10 min. Other properties of polyethylene copolymers suitable for pre-laid waterproofing sheets are also considered.

[0107] In some embodiments, sanitary products may include the polyethylene copolymers of the present disclosure. In at least one embodiment, the polyethylene copolymers suitable for sanitary products may have one or more of the following properties: a complex shear viscosity (η*) of 8,000 Pa·s to 10,000 Pa·s at 0.01 rad / s and 190°C; a complex shear viscosity (η*) of 900 Pa·s to 1,100 Pa·s at 100 rad / s and 190°C; a viscosity of 0.935 g / cm 3 Up to 0.940g / cm 3 and a melt index of 1.5 g / 10 min to 2.5 g / 10 min. Other properties of polyethylene copolymers suitable for use in sanitary products are also considered.

[0108] In some embodiments, the polyethylene copolymer or its blend is 80-150 s -1 The extrudate was provided at an apparent die (wall) shear rate of 100 Å and 80 Å without significant melt fracture as observed by visual inspection (again, even in the absence of a PPA such as a fluorinated PPA).

[0109] The polyethylene copolymers (or blends thereof) disclosed herein can be used in forming operations such as film, sheet and fiber extrusion and coextrusion as well as blow molding, injection molding and rotational molding. Films include blown or cast films formed by, for example, coextrusion or by lamination, which can be used as shrink films, adhesive films, stretch films, sealing films, oriented films, snack packaging, heavy-duty bags, grocery bags, baked and frozen food packaging, medical packaging, industrial pads, diaphragms, etc. in food contact and non-food contact applications. Fibers can include melt spinning, solution spinning and melt-blown fiber operations for use in woven or nonwoven forms to make filters, diaper fabrics, medical garments, geotextiles, etc. Extruded products can include medical tubing, line and cable coatings, pipelines, geomembranes and pool liners, etc. Molded products can include single-layer and multilayer structures in the form of bottles, cans, large hollow products, rigid food containers and toys.

[0110] The polyethylene copolymer (or its blend) can be formed into a monolayer film or a multilayer film. These monolayer films and / or multilayer films can be formed by any suitable technique, including, for example, extrusion, coextrusion, extrusion coating, lamination, blow molding and casting and other suitable techniques. The film can be obtained by a flat film or tubular film process, followed by orientation in a single axis direction or in two mutually perpendicular directions in the plane of the film.

[0111] One or more in the film layer can be oriented to the same or different degree in the horizontal and / or vertical direction.This orientation can be carried out before and / or after each layer is assembled.For example, polyethylene copolymer (or its blend) layer can be extrusion coated or laminated on the oriented polypropylene layer, or polyethylene copolymer (or its blend) and polypropylene can be coextruded into film together, then oriented.Equally, oriented polypropylene can be laminated on oriented polyethylene copolymer (or its blend), or oriented polyethylene copolymer (or its blend) can be coated on polypropylene, then optionally, if desired, combination can even further orientation.

[0112] Films include monolayer films or multilayer films. Specific end-use films include, for example, blown films, cast films, stretch films, stretch / cast films, stretch cling films, stretch hand roll films, mechanical stretch wraps, shrink films, shrink wrap films, greenhouse films, laminates, and laminated films. Exemplary films can be prepared by any conventional method known to those skilled in the art, such as by techniques for preparing blown, extruded, and / or cast stretch and / or shrink films (including, for example, shrink-on-shrink applications).

[0113] In one embodiment, the multilayer film (or multilayer films) can be formed by a suitable method. The total thickness of the multilayer film can be changed based on the desired application. A total film thickness of 5 μm to 100 μm, such as 10 μm to 50 μm, is suitable for most applications. Those skilled in the art will understand that the thickness of each layer of the multilayer film can be adjusted based on the desired end-use performance, the polymer (one or more) used, the equipment capacity and other factors.

[0114] The materials forming each layer can be coextruded through a coextrusion feed section and a die assembly to produce a film having two or more layers that adhere together but have different compositions. Coextrusion can be suitable for use in a cast film or blown film process simultaneously. Exemplary multilayer films have at least two, at least three, or at least four layers. In one embodiment, the multilayer film is composed of five to ten layers.

[0115] Embodiments of the present disclosure may be further understood by the following non-limiting examples. The following examples are presented to provide those of ordinary skill in the art with a complete disclosure and description of how to make and use aspects of the present disclosure and are not intended to limit the scope of aspects of the present disclosure. Example

[0116] The polyethylene copolymers according to one or more embodiments provided herein are produced in a continuous gas phase fluidized bed polymerization reactor.The polyethylene copolymers according to the embodiments described herein are referred to as Example (Ex.) resins.

[0117] Example resins 1-6 were produced at a pilot plant scale in "dry" mode. Example resins 1 and 2 were prepared with similar target specifications (density of about 0.937 g / cm 3 and MI of about 1 g / 10 min). Similarly, Example Resins 3 and 4 (density of about 0.937 g / cm 3 , MI is about 1.5 g / 10 min) and Example Resins 5 and 6 (density is about 0.937 g / cm 3 , MI is about 2 g / 10 min) represents a pair of samples with the same target specifications.

[0118] Table 1 shows non-limiting polymerization conditions for forming Example Resins 1-6.Polymerization is carried out in a continuous gas phase fluidized bed reactor.The fluidized bed is composed of a catalyst and growing polymer particles.The gaseous feed stream of ethylene and hydrogen is mixed with a liquid comonomer in a mixing tee arrangement pipe and introduced into the recycle gas line below the reactor bed.ICA (isopentane) is added together with ethylene and hydrogen, and is also introduced into the recycle gas line below the reactor bed.The respective flow rates of ethylene, hydrogen and comonomer are controlled to maintain a fixed composition target.The ethylene concentration is controlled to maintain a constant ethylene partial pressure.Hydrogen is controlled to maintain a constant molar ratio of hydrogen to ethylene.The concentration of each gas is measured by an online gas chromatograph to ensure a relatively constant composition in the recycle gas stream. Table 1 Ex.1 Ex.2 Ex.3 Ex.4 Ex.5 Ex.6 Residence time, h 4.9 4.9 5.3 5.3 5.7 5.7 Production rate, lbs / h 144 144 138 138 141 141 Reactor bed temperature (median), °F 195 195 195 195 195 195 Ethylene partial pressure, psia 198 198 198 198 198 198 <![CDATA[Hydrogen ratio H2 / C2, ppm / mol%]]> 9.6 9.6 10.9 10.9 11.6 11.6 Comonomer gas ratio C6 / C2, mol / mol 0.0036 0.0036 0.0038 0.0038 0.0040 0.0040 Isopentane concentration, mol% 10 10 10 10 10 10

[0119] Example resins 1-6 were compared to conventional resins. Conventional resins referred to as comparative (C.Ex.) resins include Enable TM 3505MC(C.Ex.1), Enable TM 4009MC (C.Ex.2) and Dowlex TM 2036P (C.Ex.3). Comparative resins 1 and 2 were produced via "condensation" mode. Enable TM 3505MC and Enable TM 4009MC resin is an ethylene-1-hexene copolymer available from ExxonMobil Chemical Company of Houston, TX. TM 2036P is a LLDPE available from Dow Chemical Company. Table 2 shows selected and non-limiting properties of the example resins and comparative resins. Table 2

[0120] The non-limiting 1 H NMR data show that the Example resins have higher levels of trisubstituted olefins / 1000C than the Comparative resins. For example, Example resins 1-6 have about 0.09 to about 0.12 trisubstituted olefins / 1000C, while Comparative resins 1-3 have about 0.07 trisubstituted olefins / 1000C or less. Such higher levels of trisubstituted olefins / 1000C shown by the Example resins may indicate the presence of hindered double bonds.

[0121] In addition, the example resin has a higherTM 3505MC and Enable TM 4009MC has a higher total unsaturation level. For example, the Example resin has a total unsaturation of about 0.17 to 0.23, while Enable TM 3505MC and Enable TM The total unsaturations for 4009MC are 0.16 and 0.13 respectively. The higher total unsaturation level for the example resin is surprising since the example resin has a much higher MI. Here, there may be greater potential for lowering unsaturations since the higher MI resins (2 g / 10 min vs. 1.5 g / 10 min vs. 1 g / 10 min) produced with the same catalyst have higher hydrogen / ethylene ratios in the reactor.

[0122] Non-restrictive 13 The C NMR data showed that most of the hexene in the Example resins was isolated hexene, as indicated by the triad content. For example, the [HHH] triad content of the Example resins was found to be about 0.001 mol% or less, while the [EEE] triad content ranged from about 0.969 mol% to about 0.974 mol%. The [HEE] triad content of the Example resins (about 0.017 mol% to about 0.021 mol%) was superior to that of Comparative Resin 1 (0.017 mol%) and Comparative Resin 2 (0.014 mol%). The Example resins also showed good levels of C6 / C2 content relative to the Comparative Resins, with Dowlex TM 2036P has a very low C6 content. In addition, the value of branching / 1000C follows the C6 / C2 content.

[0123] The comonomer distribution in various resins was determined based on the TREF results. 75 -T 25 The smaller difference in the values ​​reflects the narrow distribution. Here, it is found that the T 75 -T 25 The values ​​range from about 2.5° C. to about 3.2° C., compared to 2° C. (Comparative Resins 1 and 2) and 8.9° C. (Comparative Resin 3). These results may indicate that the composition distribution of the example resins is correlated with the ICA concentration.

[0124] Melt index (MI) and density data are also shown in Table 2. Here, the MI of Example Resins 1-6 was found to be much higher than that of Comparative Resins 1 and 2 and lower than that of Comparative Resin 3. Specifically, the MI of the Example Resins was determined to be about 1 g / 10 min (~1.09 and ~1.02, respectively) for Example Resins 1 and 2, about 1.5 g / 10 min (~1.61 and ~1.53, respectively) for Example Resins 3 and 4, and about 2 g / 10 min (~2.08 and ~2.06, respectively) for Example Resins 5 and 6, while Comparative Resins 1 and 2 had MIs of 0.43 g / 10 min and 0.9 g / 10 min, respectively, and Comparative Resin 3 had an MI of 2.52 g / 10 min. These results indicate that Example Resins 1-6 have lower melt viscosities than Comparative Resins 1 and 2 and are therefore easier to extrude, while Comparative Resin 3 has a lower melt viscosity (and is easier to extrude) than Example Resins 1-6. However, Comparative Resin 3 has a lower zero shear viscosity than Example Resins 1-6 (see Figure 2 ), which results in lower bubble stability during film blowing.

[0125] In addition, the high load melt index (HLMI) of Example Resins 1-6 was measured to be much higher than Comparative Resins 1 and 2, and Example Resins 3, 5 and 6 had a higher HLMI than Comparative Resin 3. The HLMI results are similar to the melt index results (melt viscosity and extrudability), but at slightly higher shear rates. The MIR of the Example Resins was measured to be about 37.1 to about 43.9.

[0126] The resin of the example is about 0.935 g / cm 3 to about 0.937 g / cm 3 The density of the embodiment resin is a relatively high density linear polyethylene (which is sometimes referred to as medium density polyethylene). The density of the embodiment resin described herein can be used in various applications, such as laminated composite pipes, sanitary products, blown breathable films, waterproof sheets, and pipe adhesives.

[0127] Table 2 also shows selected molecular weight and comonomer content data generated using GPC 4D. The total molecular weight distribution data (IR) of Example Resins 1, 4 and 6 and Comparative Resins 1-3 are plotted on Figure 1 For clarity, Figure 1Data from only one resin from each pair of example resins is included in the table. For example resins 1-6, the average molecular weight follows the observed MI trend, with the high MI (~2 g / 10 min) example resins having lower average molecular weights than the lower MI (~1 g / 10 min) resins. For example resins 1-6 and comparative resins 1 and 2, the GPC data indicate that lower molecular weights can lead to easier extrudability but lower bubble stability, while higher molecular weights can lead to greater bubble stability but less easy extrudability.

[0128] In addition, commercial ENABLE TM The presence of a small amount of long chain branching (LCB) in the grade can improve processability in cast film applications. The presence of LCB can generally provide processing advantages, such as reduced shrinkage and increased draft stability. It is found that the embodiment resins of the present disclosure can maintain such favorable LCBs, even while achieving higher density and MI. In addition, relative to those of the comparative commercial grades, the properties of the embodiment resins can result in lower head pressures and temperatures during extrusion while maintaining bubble stability, which can lead to increased output.

[0129] Viscosity flow data using SAOS data are shown in Figure 2 The examples and comparative resins were subjected to a 100 rad / s (η 100 ) and 0.01rad / s(η 0.01 ) are shown in Table 2. Shear rates approaching the range of about 100 to 1000 rad / s are typically encountered during the extrusion stage of film manufacturing. The Example resins have much lower η than Comparative Resins 1 and 2 (1844 Pa·s and 1633 Pa·s, respectively). 100 Compared with comparative resins 1 and 2, the lower η of the example resins 100 A value of η will result in lower melt pressure and thus higher extrusion rate during melt processing. 100 The values ​​are similar to those of Example Resins 1 and 2 (but higher than those of Example Resins 3-6). However, Comparative Resin 3 also has very low η compared to the Example Resins. 0.01 Value, when using a resin having η similar to that of Comparative Resin 3 0.01 This results in poor bubble stability during blown film manufacturing when using resins with high Å values.

[0130] Figure 3Van Gurp Palmen curves of example resins and comparative resins according to at least one embodiment of the present disclosure are shown. All example resins 1-6 show an inflection point in their Van Gurp Palmen curves, indicating the presence of long chain branching. Comparative resin 3 shows LLDPE without any long chain branching. Therefore, the polyethylene copolymers of the present disclosure can be characterized as having an inflection point in the Van Gurp Palmen curve.

[0131] Polyethylene polymers and articles made therefrom are described herein. In general, embodiments of MDPE polymers and articles made therefrom provide numerous advantages. The MDPE polymers described herein can be copolymers having a combination of high density, high melt index, and maintained long chain branching while also providing commercially desirable processing characteristics and extrusion of MDPE polymers.

[0132] Certain embodiments and features have been described using a set of numerical upper limits and a set of numerical lower limits. It is understood that ranges including combinations of any two values, such as any lower limit value combined with any upper limit value, any combination of any two lower limits, and / or any combination of any two upper limits are contemplated unless otherwise indicated. Certain lower limits, upper limits, and ranges appear in one or more claims below. All numerical values ​​are "about" or "approximately" indicative values, and take into account experimental errors and deviations that would be expected by one of ordinary skill in the art.

[0133] All priority documents are fully incorporated herein by reference for all purposes and in all jurisdictions permitting such incorporation, and to the extent such specification is consistent with the present disclosure. In addition, all documents and references cited herein (including test procedures, publications, patents, journal articles, etc.) are incorporated herein by reference in their entirety, provided that their disclosures are not inconsistent with the present disclosure.

[0134] Likewise, whenever a composition, element, or group of elements is preceded by the transitional term "comprising," it should be understood that the same composition or group of elements preceded by the transitional term "consisting essentially of," "consisting of," "selected from," or "is" is also contemplated, and vice versa. Unless otherwise specified, the phrase "consisting essentially of" does not exclude the presence of other steps, elements, or materials (whether or not specifically mentioned in this specification), as long as these steps, elements, or materials do not affect the basic and novel characteristics of the invention, and further, the phrase does not exclude impurities and variations normally associated with the elements and materials used.

[0135] While the foregoing has been described in terms of a number of embodiments and examples, those skilled in the art, after reading this disclosure, will appreciate that other embodiments can be devised without departing from the scope and spirit of this disclosure.

Claims

1. Polyethylene copolymer, comprising: Ethylene units; and 1 to 8 wt% of C3-C8 alpha-olefin comonomer units, the polyethylene copolymer having: 0.934g / cm 3 Up to 0.945g / cm 3 density; A melt index (MI, measured at 190°C and 2.16 kg load according to ASTM D1238) greater than 0.9 g / 10 min and less than or equal to 2.5 g / 10 min; A composition distribution breadth index of 75% or greater; a molecular weight distribution (MWD, Mw / Mn) of 2 to 8; and Melt Index Ratio (MIR) in the range of 30 to 75, wherein MIR is the ratio of High Load Melt Index (HLMI, ASTM D1238, at 190°C, 21.6 kg) to Melt Index (MI, ASTM D1238, at 190°C, 2.16 kg).

2. The polyethylene copolymer of claim 1 having long chain branching.

3. The polyethylene copolymer of claim 1 or claim 2, having an inflection point in a Van Gurp Palmen plot of phase angle versus complex modulus (Pa) of the polyethylene copolymer.

4. The polyethylene copolymer of any one of claims 1-3, wherein the polyethylene copolymer has an alpha parameter of 230 to 1,000 as determined by Equation 1: α parameter = (MIR*η 0.01 / η 100 )*(T 75 -T 25 ) / MWD (Equation 1) Where MIR is the melt index ratio, η 0.01 is the complex shear viscosity (η*) at 0.01 rad / s and 190°C, η 100 is the complex shear viscosity (η*) at 100 rad / s and 190°C, T 75 -T 25 It is T 75 -T 25 Value, where T 25 is the temperature at which 25% of the eluted polyethylene copolymer is obtained using temperature-increasing elution fractionation, T 75 is the temperature at which 75% of the eluted polyethylene copolymer is obtained using temperature increasing elution fractionation, and MWD is the molecular weight distribution.

5. The polyethylene copolymer of any one of claims 1 to 4, wherein the polyethylene copolymer has 0.09 to 0.12 trisubstituted vinylene groups / 1000 carbon atoms.

6. The polyethylene copolymer of any one of claims 1 to 5, wherein the polyethylene copolymer has one or more of the following properties: 95 mol % to 99 mol % [EEE] triad content; 1.4 mol % to 2.2 mol % [HEE] triad content; 0.7 mol % to 1 mol % [EHE] triad content; 0.1 mol % or less of [HHH] triad content; 0.05 mol % or less of [HEH] triad content; or 0.05 mol% or less [EHH] triad content.

7. The polyethylene copolymer of any one of claims 1 to 6, wherein the polyethylene copolymer has a molecular weight of 0.935 g / cm 3 Up to 0.938g / cm 3 density.

8. The polyethylene copolymer of any one of claims 1 to 6, wherein the polyethylene copolymer has a molecular weight of 0.937 g / cm 3 Up to 0.94g / cm 3 density.

9. The polyethylene copolymer of any one of claims 1 to 8, wherein: The C3-C8 α-olefin comonomer unit is a 1-hexene unit; and The polyethylene copolymer comprises 92 wt% to 99 wt% ethylene.

10. The polyethylene copolymer of any one of claims 1 to 9, wherein the polyethylene copolymer further has: MI of 0.9 g / 10 min to 2 g / 10 min; 2℃ to 10℃ T 75 -T 25 value; A melt index ratio (MIR, HLMI / MI) of 35 to 45; or A combination of them.

11. The polyethylene copolymer of any one of claims 1 to 9, wherein the polyethylene copolymer further has one or more of the following properties: (a) MI of 1 g / 10 min to 2 g / 10 min; (b) T between 1.5°C and 4°C 75 -T 25 value; (c) a high load melt index (HLMI, measured according to ASTM D1238 at 190° C. and 21.6 kg load) of 35 g / 10 min to 80 g / 10 min; (d) a melt index ratio (MIR, HLMI / MI) of 37 to 44; (e) a weight average molecular weight (M) of 70,000 g / mol to 90,000 g / mol W );or (f) a number average molecular weight (Mn) of 15,000 g / mol to 30,000 g / mol.

12. The polyethylene copolymer of claim 11 having all of properties (a) to (f).

13. The polyethylene copolymer of any one of claims 1-12, wherein the polyethylene copolymer has a HLMI of 40 g / 10 min to 50 g / 10 min.

14. The polyethylene copolymer of any one of claims 1-12, wherein the polyethylene copolymer has a HLMI of 65 g / 10 min to 80 g / 10 min.

15. The polyethylene copolymer of any one of claims 1 to 14, wherein the polyethylene copolymer has: A complex shear viscosity (η*) at 0.01 rad / s and 190° C. of 8,000 Pa·s to 25,000 Pa·s; and Complex shear viscosity (η*) at 100 rad / s and 190° C. of 900 Pa·s to 1,500 Pa·s.

16. An article comprising the polyethylene copolymer of any one of claims 1 to 6.

17. The article of claim 16, wherein: The article is a cast film or a blown film; and The polyethylene copolymer has: 0.935g / cm 3 Up to 0.938g / cm 3 density; and Melt index of 1.1 g / 10 min to 1.3 g / 10 min.

18. The article of claim 16, wherein: The article is a cast film or a blown film; and The polyethylene copolymer has: 0.935g / cm 3 Up to 0.938g / cm 3 density; and Melt index of 1.8 to 2.0 g / 10 min.

19. The article of one of claims 17 or 18, wherein the blown film is substantially free of perfluoroalkanes or polyfluoroalkanes.

20. The article of claim 16, wherein: The article is a laminated composite pipe; and The polyethylene copolymer has: Complex shear viscosity (η*) at 0.01 rad / s and 190° C. of 15,000 Pa·s to 25,000 Pa·s; Complex shear viscosity (η*) at 100 rad / s and 190°C of 1,100 Pa·s to 1,300 Pa·s; 0.935g / cm 3 Up to 0.942g / cm 3 density; and Melt index of 1 g / 10 min to 1.5 g / 10 min.

21. The article of claim 16, wherein: The article is a hygiene product; and The polyethylene copolymer has: Complex shear viscosity (η*) at 0.01 rad / s and 190° C. of 8,000 Pa·s to 10,000 Pa·s; Complex shear viscosity (η*) at 100 rad / s and 190°C of 900 Pa·s to 1,100 Pa·s; 0.935g / cm 3 Up to 0.940g / cm 3 density; and Melt index of 1.5 g / 10 min to 2.5 g / 10 min.

22. The article of claim 16, wherein: The product is a pre-laid waterproof sheet; and The polyethylene copolymer has: 0.935g / cm 3 Up to 0.945g / cm 3 density; and Melt index of 1.0 g / 10 min to 1.5 g / 10 min.

Citation Information

Patent Citations

  • Method for determining a stickiness temperature of a resin

    US10029226B2

  • Metallocene-produced polyethylene for glossy plastic containers

    US20040121098A1

  • Linear low density polymer blends and articles made therefrom

    US20070260016A1

  • Ethylene-Based Polymers and Articles Made Therefrom

    US20150232589A1

  • Catalyst Systems and Polymerization Processes for Using the Same

    US20190119413A1